The Lateral Antebrachial Neurocutaneous Flap: A Cadaveric Study and Clinical Applications - Kanchanathepsak, Thepparat; Rojpitipongsakorn, Chanakarn; Tawonsawatruk, Tulyapruek; Suppaphol, Sorasak; Watcharananan, Ittirat; Tuntiyatorn, Panithan (Journal of Reconstructive Microsurgery, 2020)
Background The neurocutaneous flap is an axial pattern flap that receives a vascular supply from a vessel along its cutaneous nerve and has favorable outcomes when used for soft tissue reconstruction in the upper extremities. The neurocutaneous flap depends on the lateral antebrachial cutaneous nerve (LACN) and its retrograde-flow has been studied via cadaveric dissection. The aim of this study is to prove the vascularity of the lateral antebrachial neurocutaneous (LABN) flap.Methods The distally based LABN flap was created in 18 upper limbs (12 cadavers). The skin flap was dissected at the proximal half of the forearm and then diluted methylene blue was injected through the brachial artery. The pedicle of the flap on the distal half of the forearm was dissected along the LACN for the anatomical study of the perforating branches, paraneural vessels, and flap territory.Results The mean age of cadavers was 74.1 years (nine males). The mean distance of most distal and proximal perforating branches from the radial styloid process were 2.32 ± 0.59 and 11.17 ± 1.72 cm, respectively. The mean total number of perforating branches was 7.4, which abundantly appeared approximately 4 to 5 cm from the radial styloid process. The mean flap territory was 8.64 ± 0.82 cm in width and 10.50 ± 1.90 cm in length. The mean forearm circumference was 24.84 ± 1.52 cm, and mean forearm length was 24.74 ± 1.8 cm.Conclusion This study ensured that retrograde-flow via the neurocutaneous artery could be provided through the vascularity of the LABN flap, which suggests that the pivot point of the flap should not extend beyond 5 cm proximal to the radial styloid process. The LABN flap is a useful alternative method for performing soft tissue reconstruction in hand and wrist defects without sacrificing the major vessels.
Keywords: neurocutaneous flap; lateral antebrachial cutaneous nerve; paraneural vessels; distally based flap; retrograde-flow